Recycling of Kepok Banana Peel Waste (Musa acuminata Var. balbisiana.) and Compost Quality Analysis by Atomic Absorption Spectrophotometry (AAS) - Tomas, Jeri; Sari , Mistia; Junialdi, Rezi; Edinov, Sunny (The Future of Education Journal, 2025)
The purpose of this study was to investigate the composting process from banana peel waste using EM4 activator and cow dung. In addition, the water content, C, N, phosphorus (P), potassium (K), and C/N ratio in the resulting compost were also examined. The composting system was made in three forms of treatment, namely banana peel with a mixture of cow dung in a ratio of 5:1, and banana peel with EM4 in a ratio of 5:1, and banana peel with cow dung and EM4 in a ratio of 5:1:1. The three treatments were measured in a time span of seven days, fourteen days, and twenty-one days. The parameters measured were temperature, water content, pH, Carbon, Nitrogen, Potassium, and Phosphorus content. And compared to the standards set by SNI number 19-7-30-2004. The results obtained in the first twenty days with the addition of cow dung and EM4 showed that the use of cow dung and EM4 activators can effectively accelerate the composting rate compared to compost without activators and compost with a mixture of cow dung alone, where the compost with the addition on the twentieth day has formed, marked by a C/N ratio of 21.32% has met the standards set by SNI. The nutrient content of kepok banana peels generally meets the standards set by SNI 19-7030-2004. The nutrient content of patchouli compost using EM4 activator in the first twenty-one days was C-organic 19.82%, 20.37%, 21.32% (meeting the standard), N 0.98%, 1.05%, 1.12% (meeting the SNI standard), Potassium 0.83%, 1.04%, 1.23% (meeting the SNI), Phospor 0.109%, 0.125%, 0.132% (meeting the SNI standard), C/N ratio 20.22%, 19.4%, 19.03% (meeting the SNI standard).